skeeter Senior Member Joined Dec 15, 2005 Messages 2,396 Apr 26, 2006 #2 1. csc(2x) = 1/sin(2x) = 1/(2sinx*cosx) = (1/2)(1/sinx)(1/cosx) = ? 2. cos(2x) + cosx = 0 2cos<sup>2</sup>x - 1 + cosx = 0 2cos<sup>2</sup>x + cosx - 1 = 0 (2cosx - 1)(cosx + 1) = 0 hard part is done ... you finish it up.

1. csc(2x) = 1/sin(2x) = 1/(2sinx*cosx) = (1/2)(1/sinx)(1/cosx) = ? 2. cos(2x) + cosx = 0 2cos<sup>2</sup>x - 1 + cosx = 0 2cos<sup>2</sup>x + cosx - 1 = 0 (2cosx - 1)(cosx + 1) = 0 hard part is done ... you finish it up.